Effects of buspirone on posthypoxic ventilatory behavior in the C57BL/6J and A/J mouse strains - Yamauchi, Motoo (American Physiological Society, 2008)
Buspirone, a partial agonist of the serotonergic 5-HT(1A) receptor, improves breathing irregularities in humans with Rett syndrome or brain stem injury. The purpose of this study was to examine whether buspirone alters posthypoxic ventilatory behavior in C57BL/6J (B6) and A/J mouse strains. Measurements of ventilatory behavior were collected from unanesthetized adult male mice (n = 6 for each strain) using the plethysmographic method. Mice were given intraperitoneal injections of vehicle or several doses of buspirone and exposed to 2 min of hypoxia (10% O(2)) followed by rapid reoxygenation (100% O(2)). Twenty minutes later, mice were tested for hypercapnic response (8% CO(2)-92% O(2)). On a separate day, mice were injected with the 5-HT(1A) receptor antagonist 4-iodo-N-{2-[4-(methoxyphenyl)-1-piperazinyl] ethyl}-N-2-pyridinylbenzamide (p-MPPI) before the injection of buspirone, and measurements were repeated. In separate studies, arterial blood-gas analysis was performed for each strain (n = 12 in B6 and 10 in A/J) with buspirone or vehicle. In both strains, buspirone stimulated ventilation at rest. In the B6 mice, the hypoxic response was unchanged, but the response to hypercapnia was reduced with buspirone (5 mg/kg; P < 0.05). With reoxygenation, vehicle-treated B6 exhibited periodic breathing and greater variation in ventilation compared with A/J (P < 0.01). In B6 animals, ≥3 mg/kg of buspirone reduced variation and prevented the occurrence of posthypoxic periodic breathing. Both effects were reversed by p-MPPI. Treatment effect of buspirone was not explained by a difference in resting arterial blood gases. We conclude that buspirone improves posthypoxic ventilatory irregularities in the B6 mouse through its agonist effects on the 5-HT(1A) receptor.